The Influence of Modern Concepts that Emerged at the End of the 19th Century on the Social Life of the Turkestan Region - Yakhyo Abdurakhmanov Ubaydulloyevich (Pubmedia Social Sciences and Humanities, 2025)
The purpose of this study is to analyze the emergence and influence of modern concepts that appeared at the end of the 19th and beginning of the 20th centuries on the social, political, and intellectual life of the Turkestan region. Using a qualitative historical-analytical method, the research examines how modernist ideas—originating in the Muslim world, particularly from reformist movements in Egypt, Turkey, and India—were adapted by local intellectuals and Jadid reformers to promote social transformation. The study draws on historical documents, scholarly works, and reformist writings to assess how modernization affected education, law, political thought, and national consciousness among the peoples of Turkestan. The results show that the spread of reformist thought led to the rise of new educational systems, increased political awareness, and the development of socio-religious reforms that bridged traditional Islamic principles with modern rationalist ideas. The study concludes that these reformist concepts played a key role in shaping the intellectual and cultural revival of Turkestan, laying the foundation for national awakening and modern identity formation in Uzbekistan and Central Asia.